Pathological features of the 7T post‐mortem MRI white matter hyperintensity penumbra. (December 2021) - Silbert, Lisa C; Roese, Natalie E; Hurworth, Justin; Lahna, David; Krajbich, Victoria; Schwartz, Daniel L; Woltjer, Randy L
Abstract: Background: T2‐weighted white matter hyperintensities (WMH) are ubiquitous with age, and associated mild cognitive impairment and dementia. Recent studies have demonstrated altered microstructural integrity and perfusion within the normal appearing white matter (NAWM) surrounding WMHs, the "WMH penumbra", indicating more widespread WM tissue damage than is commonly observed on routine MRI. While common pathological features associated with in vivo WMH burden have been described, histochemical (HC) features obtained by directly targeting the WMH core and surrounding NAWM remain largely uncharacterized. Method: Post mortem (PM) 7T MRI was obtained on 6 brain hemispheres from Oregon Alzheimer's Disease Research Center subjects (Table 1). Fifty‐three WMH and NAWM penumbra regions of interest (ROI) were identified from 11 brain regions and targeted for HC analysis (Table 2). Tissue samples were stained with hematoxylin & eosin‐luxol fast blue (HELFB), aquaporin‐1 (AQP1), and vimentin and scanned for quantitative ROI analysis. WMHs were segmented on T2‐weighted images, and WMH masks were dilated by 1mm increments to define a 5 mm NAWM penumbra and coregistered to IHC images (Figure 1). Digitalized IHC mages were assessed quantitatively using mean pixel saturation (AQP1, Vimentin) or thresholded area coverage (HELFB). Mixed effects models were used to examine mean differences in IHC staining between WMH and the NAWM penumbra and change in HC staining within the NAWM with distance from WMHs. Analyses were adjusted for global WMH burden, and individual slide effects to account for potential differences in staining. Result: WMHs demonstrated increased vimentin, and decreased AQP1 and HELFB staining, compared with the NAWM penumbra. Within the NAWM penumbra, there was an increase in vimentin and a decrease in AQP1 and myelin content with closer proximity to WMHs (Figure 2). Conclusion: The MRI‐identified NAWM region surrounding WMHs show a gradient of demyelination and astrocytopathy with distance from WMHs. Findings confirm the presence of the WMH penumbra consisting of damaged tissue that is likely vulnerable to further injury over time that could be a target for intervention in life. Results suggest that MRI visible WMHs are a state marker of more widespread tissue degeneration that may contribute to cognitive decline in older individuals.